Hybrid de novo Genome Assembly of Erwinia sp. E602 and Bioinformatic Analysis Characterized a New Plasmid-Borne lac Operon Under Positive Selection - Xia, Yu; Wei, Zhi-Yuan; He, Rui; Li, Jia-Huan; Wang, Zhi-Xin; Huo, Jun-Da; Chen, Jian-Huan (Frontiers in Microbiology, 2021)
Our previous study identified a new β-galactosidase in Erwinia sp. E602. To further understand the lactose metabolism in this strain, the de novo genome assembly was conducted by using a strategy combining Illumina and Pacbio sequencing technology. The whole genome of Erwinia sp. E602 include a 4.8 Mb chromosome and a 326 kb large plasmid. A total of 4,739 genes, including 4,543 protein-coding genes, 25 rRNAs, 82 tRNAs, and 7 other ncRNAs genes were annotated. The plasmid was the largest one characterized in genus Erwinia by far, and it contained several genes and pathways responsible for lactose metabolism and regulation. Moreover, a new plasmid-borne lac operon was identified in this strain. The newly identified lac operon lacked a typical β-galactoside transacetylase (lacA) gene. Phylogenetic analysis showed that the genes lacY and especially lacZ were under positive selection, indicating the adaptation of lactose metabolism to the environment in Erwinia sp. E602. Our current study demonstrated that the hybrid de novo genome assembly using Illumina and Pacbio sequencing technologies, as well as the metabolic pathway analysis, provided a useful strategy for better understanding of the evolution of undiscovered microbial species or strains.